Bebes and the Bear : Gene Stallings, Coach Bryant, and Their 1968 Cotton Bowl Showdown - Suresha, Ron Jackson (Book collections on Project MUSE., 2019)
"A ground-breaking, historical narrative that chronicles the lives and the lifelong relationship of legendary football coach Paul W. "Bear" Bryant and his most ardent coaching disciple, Gene Stallings. It concludes with their highly publicized showdown at the 1968 Cotton Bowl Classic - a matchup the national media hails the mentor vs. the pupil"--